An assessment of determinants of adaptive capacity to climate change/variability in the rural savannah of Ghana - Yaro, J.A.; Teye, J. K.; Bawakyillenuo, S. (Springer, Cham, 2016)
The varied stressors posed by climate change and variability to the livelihoods of agrarian societies in many developing countries call for an examination of the determinants of adaptive capacity. Data collected through a questionnaire survey, in-depth interviews and focus group discussions, is used to explain the determinants of adoption of five major adaptation strategies. The analysis reveals that while adaptive capacity in the northern savannah zone is generally low due to high levels of poverty and poor state presence, it varies spatially resulting from locational, individual and community socio-economic and institutional factors. Adaptive capacities are rooted in the nature of household and community assets as well as societal rules and policies. Both community level factors and characteristics of individual farmers condition the idiosyncratic variables defining the capacities to adopt specific adaptation strategies to climate change threats. Important farmer characteristics that determine critical adaptation strategies in the northern savannah include age, sex, assets, family size, size and type of land, skills/education, and perception of climatic changes. This paper recommends that local resilience building mechanisms be scaled up while modern mechanisms should be introduced for dealing with the impacts of climate change.
Keywords: Climate Change; Adaptive Capacity; Adaptation Strategy; Agronomic Practice; Male Farmer